Anti-inflammatory effect of combined tetramethylpyrazine, resveratrol and curcumin in vivo - Long Chen; Tianjun Liu; Qiangsong Wang; Juan Liu (BMC, 2017)
Abstract Background Resveratrol and curcumin, as natural flavones products, have good therapeutic effect in acute and chronic inflammation; on the other hand, tetramethylpyrazine (TMP) has angiogenesis and vessel protection effect as well as anti-inflammatory function. In this paper, the anti-inflammatory effect of the tetramethylpyrazine, resveratrol and curcumin (TRC) combination in acute and chronic inflammation was reported in vivo. Methods The dose of the combined three natural products was optimized based on the acute paw swelling mouse model with a Uniform Design methodology. The therapeutic effect of TRC combination on chronic inflammation was investigated by using the collagen-induced arthritis (CIA) rat model based upon the following indexes: the volume of paw swelling, arthritis score, serum mediators and histological examination as well as immunohistochemical staining. The levels of alanine aminotransferase (ALT) and aspartate transaminase (AST) in serum were measured and the pathological sections of liver and kidney were analysed. LD50 was measured based on the acute oral toxicity (AOT) standard method. Results The best formulation was the three components combined at the same mass proportion revealed by the Uniform Design methodology. This combination could significantly reduce the paw swelling in acute paw swelling mouse model, could reduce paw swelling and alleviate the damage in joint structural of ankle, cartilages and fibrous tissue in CIA rat model. The dose relationship was clear in both cases. Immunohistochemical staining of ankle tissue revealed that TRC combination was able to inhibit the expression of NF-κB p65 and TNF-α which were closely related to the inflammatory process. Analysis of serum mediators revealed TRC combination could inhibit the production of TNF-α, IL-1β, and IL-6 in the serum. Toxic study revealed this formulation was low toxic, LD50 was larger than 5 g/kg, both the level of ALT and AST and histopathology in the liver and kidney exhibited no distinctions between the TRC combination and the blank group, no mortality occurred at the administered doses of 5 g/kg. Conclusions The results showed this formulation could provide a novel potent treatment for acute and chronic inflammation (RA) without side effect like gastric injury occurring in NSAIDs.